The Brownie Scouts at Snow Valley - Wirt, Mildred A. (Mildred Augustine), 1905-2002 (Salt Lake City, UT : Project Gutenberg, 2016)
"The Brownie Scouts at Snow Valley" by Mildred A. Wirt is a children's novel written in the mid-20th century. The story centers around a group of young girls who are part of the Brownie Scouts, especially focusing on Connie Williams and her interactions with her troop, as well as her friend Veve McGuire, who longs to join the group after initially rejecting the idea. The book captures their adventures, particularly as they prepare for a trip to Snow Valley during winter time, dealing with themes of friendship, belonging, and the joys of childhood. At the start of the tale, the Brownies are seen engaging in creative activities at Connie's home, which is interrupted by Veve, who wishes to join them in outdoor play. While most of the Brownies ignore her, Connie invites her to play and even suggests that she join the troop. The narrative unfolds with various escapades, including a sledding misadventure with Veve that leads to a call for police assistance. This opening sets the stage for both the excitement of winter activities and the dynamics of friendship, particularly as Veve's journey unfolds from outsider to potential member of the Brownie troop amidst plans for their adventure to Snow Valley. (This is an automatically generated summary.)
Release date is 2016-04-12
Produced by Stephen Hutcheson, Dave Morgan and the Online Distributed Proofreading Team at http://www.pgdp.net
Keywords: Vacations -- Juvenile fiction; Winter -- Juvenile fiction; Mystery fiction; Minnesota -- Juvenile fiction; Brownie Girl Scouts -- Juvenile fiction